Analysis of Raw Material Inventory Control Using the EOQ (Economic Order Quantity) Method in the CV. Alda - YUNUS (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to determine the mechanism for determining raw material inventory, the number of raw material orders and the most optimal order frequencies in the CV. Alda The method used in this study is a quantitative descriptive method used to make a systematic, factual and accurate picture of an object to be studied. The data in this study are in the form of company inventory report data. Calculation results show that there are significant differences between the EOQ values ​​each year. EOQ is gradually experiencing a downward trend. The decrease is due to differences in inventory levels and costs attached to these inventories, especially in the level of demand for raw materials each year. By using the EOQ method, companies canknow when to order and how much to order, so as to minimize costs